Mathematics in Applied Informatics Education - New Choices and Challenges - Michal Kaukic (Communications - Scientific letters of the University of Zilina, 2006)
In this paper, new ways of teaching Mathematics, which have been opened by the widespread of computers and notebooks and also by adequate software tools, are discussed. Based on our experience, we advocate the use of Open Source software as the mainstream tools in Mathematics and Informatics education. We give the more concrete examples of tools, used for teaching of Numerical Analysis topics, which can be successfully explored also for majority of other subjects in Applied Informatics and Mathematics. Some recommendations for the choices of suitable software and for further coordination in this field are given.